Pure and almost pure NIR emission of Tm and Tm, Yb–CeO2 under UV, X-ray and NIR up-conversion excitation: key roles of level selective antenna sensitization and charge-compensation. Issue 46 (28th September 2015) - Avram, Daniel; Cojocaru, Bogdan; Urda, Adriana; Tiseanu, Ion; Florea, Mihaela; Tiseanu, Carmen
Abstract : A first study that correlates the down- and up-conversion emission properties of lanthanide(s)-(co) dopants with the CeO2 structure. Abstract : Herein, we report on the pure and almost pure near-infrared (NIR) emission at around 807 nm observed for Tm(Yb) (co)-doped CeO2 nanoparticles (NPs) under UV, X-ray and NIR up-conversion excitation. The optical responses are attributed to the low-lying charge-transfer of CeO2 that acts as a selective antenna sensitizer of the Tm 3 H4 emission and Yb doping that lowers the local symmetry at Tm sites and introduces additional phonon modes. Selective antenna sensitization is also observed for Er/Ho (Yb) (co)-doped CeO2 NPs. To the best of our knowledge, this is a first study which correlates the down- and up-conversion emission properties of lanthanide(s)-(co) dopants with the CeO2 structure highlighting also the outstanding potential of these NPs in high-penetration tissue imaging and therapy.